2020
DOI: 10.1177/2309499020918170
|View full text |Cite
|
Sign up to set email alerts
|

Same-day Bilateral Total Knee Arthroplasty Did Not Increase 90-day Hospital Returns

Abstract: Purpose: Bilateral total knee arthroplasty (TKA) can be performed in patients with bilateral knee arthritis. Outside of nationwide database studies, which have limitations, few studies have compared outcomes for same-day versus staged TKA. We sought to compare patient outcomes at a single tertiary referral center. Methods: The institutional database was queried from March 2014 to December 2017 for primary TKA. Patients undergoing bilateral procedures were stratified by same-day versus staged; length of stay (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Hernandez et al found no correlation between the BMI, age, and the ASA score and hospital returns at 90 days after SiBTKA [ 16 ]. In addition, according to Takagawa S and coll., the ASA score and the BMI did not interfere with postoperative rehabilitation protocols in patients undergoing SiBTKA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hernandez et al found no correlation between the BMI, age, and the ASA score and hospital returns at 90 days after SiBTKA [ 16 ]. In addition, according to Takagawa S and coll., the ASA score and the BMI did not interfere with postoperative rehabilitation protocols in patients undergoing SiBTKA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, simBTKA could be associated with higher blood transfusion rates, mortality, and pulmonary embolism, but lower frequency of infection and revision of the procedure compared to staged bilateral total knee arthroplasty. 7 …”
Section: Discussionmentioning
confidence: 99%
“…3 However, simBTKA could be associated with higher blood transfusion rates, mortality, and pulmonary embolism, but lower frequency of infection and revision of the procedure compared to staged bilateral total knee arthroplasty. 7 Studies on simBTKA in Saudi Arabia are scarce. We evaluated the outcomes in 469 patients who had simBTKA in a single tertiary referral center.…”
mentioning
confidence: 99%
“…Other considerations for this case are the options for staged vs simultaneous bilateral TKAs and the possibility for outpatient TKA in severe Blount disease. Although some studies have shown higher risk of medical complications, thrombotic events, and need for blood transfusions with simultaneous bilateral TKA [ [26] , [27] , [28] ], other studies have shown that simultaneous bilateral TKA has an acceptable risk, especially in appropriately selected patients [ 29 , 30 ]. For this case, we performed staged TKAs; however, it should be noted that due to the severity of the patient’s deformity, the patient had an approximately 20-mm LLD after the first TKA, which made rehabilitation and ambulation difficult; however, this may have possibly avoided the medical complications associated with simultaneous TKA.…”
Section: Discussionmentioning
confidence: 99%